FANATISME SUPORTER SEPAK BOLA TERHADAP PERILAKU AGRESI - Anindya Wiralarasati; Chelsea Gita Kharisma; Muhammad Nanda; Sofyan Hutamam; M.Delvin Oknanda (CV. Doki Course and Training, 2023)
The development of the sports world is currently running very fast and the growth of the sports industry is accompanied by an increase in the number of followers. Many fans watch football. The large number of soccer fans is because soccer is a sport that is very popular with all groups, both children and adults. an overly enthusiastic attitude towards a point of view or problem. This attitude may be based on his thoughts and understandings, which do not change or remain the same. According to Winston Churchill,